IMPLEMENTATION OF AQIDAH AKHLAK LEARNING USING THE CONTEXTUAL LEARNING MODEL IN MA AN-NUR MALANGBONG GARUT DISTRICT - Lalan Jaelani (International Journal of Islamic Khazanah, 2019)
Aqidah learning morality that there is prioritizing cognitive aspects, both concerning the divinity and humanity that want to be instilled and developed into students themselves. The purpose of this study is to find out and analyze; (1) Aqidah moral learning design using a contextual approach, (2) implementation of Aqidah morality learning (3) evaluating Aqidah morality learning using a contextual learning approach, (4) supporting and inhibiting factors, (5) advantages and disadvantages and (6) the effectiveness of contextual learning approaches in the subjects of Aqidah Morals to shape the Islamic character of students. Using descriptive qualitative methods with the type of analytic descriptive research. The data collection tool was obtained using: observation, interview, and study documentation. The data analysis procedures performed are data reduction, data presentation, drawing conclusions or verification. The results of this study show that the design of contextual learning in the subjects of Aqidah Akhlak uses the components of the Contextual Teaching and Learning (CTL) stages, namely constructivism (constructivism), finding (inquiry), asking (questioning), learning community (learning community), modelling (modelling), reflection (reflection), and actual assessment (authentic assessment). The implementation of Aqidah Akhlak learning by using a contextual approach in MA An-Nur Malangbong is following the learning design. While the inhibiting factors include: difficulty analyzing individual student differences, not all are suitable for using a contextual approach, as well as difficulties in conducting evaluation and time management that requires a lot of time. Meanwhile, the contextual approach to the subjects of Aqidah Akhlak carried out at MA An-Nur Malangbong for the formation of Islamic character in students can be said to be very effective. This can be seen from the increase in their learning outcomes for the five Islamic characters analyzed, namely honesty, discipline, responsibility, cooperation and courtesy, experiencing an average increase from 2.44 to 3.3.